'Had a lovely week at #conference2018 ': An Analysis of Interaction through Conference Tweets. (April 2020) - Luzón, María José; Albero-Posac, Sofía
Twitter has become a common feature of academic conferences, used by organizers to provide information about the conference and by attendees to engage in discussion about the conference topics, share information, and create social links and networks within the community. This study examines the tweets from two conferences in Applied Linguistics in order to analyse the networked language practices of scholars using Twitter during conferences. More specifically, in this study we address the following questions: (i) what are the purposes for which scholars in this disciplinary community use Twitter during conferences? (ii) how are different semiotic resources (e.g. linguistic forms, pictures, videos, embedded slides) combined to orchestrate meaning and achieve these various rhetorical purposes? We also look at how Twitter features (hashtags, replies, retweets, mentions) contribute to these rhetorical purposes. The analysis reveals that tweets are mostly intended to create and maintain cohesive links or to encourage peers to perform specific actions. In order to achieve these functions scholars compose their tweets by using a variety of (linguistic and non-linguistic) expressions of stance and engagement (Hyland, 2005). We suggest that, given the increasingly important role of social media for scholarly communication, a central concern of EAP courses should be to help students develop the competence of composing multimodal texts. Scholars need to understand the ways in which the multiple semiotic resources available to them in social media can be used effectively to engage other members of the community in these new digital contexts.